Towards a more uniform approach to parenting coordination in South Africa - De Jong, Madelene (Potchefstroom Electronic Law Journal, 2022)
Because of the need to mitigate the damage done to children by chronic conflict between co-parents after divorce or family breakdown, the process of parenting coordination has been embraced by South African courts. In terms of the process, a parenting coordinator will first attempt to facilitate resolution of the parenting disputes by agreement of the parties, but if this attempt fails, the parenting coordinator has the power to make directives regarding the disputes which are binding on the parties until a competent court directs otherwise or the parties jointly agree otherwise. Although parenting coordination has flourished over the past decade, there still seems to be uncertainty and a lack of uniformity about various aspects regarding the process and the role and functions of a parenting coordinator. First of all, we have the Guidelines on the Practice of Parenting Coordination in South Africa (SA Guidelines), drafted by a task team of the National Accreditation Board for Family Mediators (NABFAM) to provide guidance for parenting coordinators concerning minimum qualifications, ethical obligations and conduct, practice and procedure, and children’s participation in the process. In addition, the South African Law Reform Commission published the draft Family Dispute Resolution Bill, 2020, which deals with the process of parenting coordination in Chapter 7. Very importantly, we also have various court decisions dealing with parenting coordination in South Africa, which provide some guidance. However, the SA Guidelines, the provisions of Chapter 7 of the Bill and our court decisions are not always aligned and provide different answers to important underlying theoretical questions about various issues, such as the circumstances under which a parenting coordinator should be appointed; the issues that could be dealt with by a parenting coordinator; whom to appoint as a parenting coordinator; the approach to be followed in the parenting coordination process; the inclusion of children in the parenting coordination process; the nature of the parenting coordination process; confidentiality in the process; and a parenting coordinator’s relationship with the court and the parties’ legal representatives. A lack of consensus regarding these issues has given rise to diverse practices among professionals and confusion for all involved in the parenting coordination process. This article therefore endeavours to provide more clarity and certainty on these issues, taking international best practice into account.